Aplicação das matrizes no processamento de imagens usando o software Scilab - Soares, José Alexandre Fernandes (2019)
We live in a digital age and computer science is present in our everyday life as much as Mathematics, so these two fundamental segments of daily life have merged or united to bring more quality of life to contemporary man. Recently, digital image processing techniques have been employed to de ne a large number of problems that require methods capable of improving visual information for human analysis and interpretation. In summary, it can be concluded that this study has as general objective to know the aspects of the application of matrices in the image processing using Scilab software and to understand the importance of this whole process involving matrix and image. Understanding how the array can a ect an image. In order to reach the proposed objectives, the methodology to which this study refers is a literature review composed of researches carried out in books by several renowned authors as described in our reference. In the second part, treatment will be given in the images from the database through the Scilab program. We will use lters on the images and, consequently, analize the results of the on goings of these same images